Ethics-Driven Character Development in Pharmacy Students: A Conceptual Framework. - Ashiq, Kanwal; Iqrah Ashfaq; Abubakar Munir (Spanish Journal of Medical Education, 2026)
Objectives: Character development is an essential but often overlooked aspect of pharmacy education. While clinical skills and technical knowledge are paramount, pharmacists' professional and ethical behavior directly influences patient care, public trust, and the overall improvement of the healthcare system. This communication emphasizes the importance of developing strong character values among pharmacy students to produce ethical, competent professionals. It proposes an ethics-driven framework integrating professionalism, professional identity formation, and virtue ethics. It also identifies key traits essential for professional development. Methods: This brief communication presents a perspective grounded in the existing literature and established frameworks on character education in pharmacy, highlighting key traits essential to professional development. The themes were synthesized to emphasize the core attributes required for effective professional growth. Results: The findings highlight the importance of character development in pharmacy students, particularly integrity, compassion, responsibility, and perseverance. Integration of character education into pharmacy curricula can support ethical decision-making, effective communication, and leadership skills. Ethical dilemmas in pharmacy practice require strong moral reasoning and patient-centered commitment. Reflective practice and mentorship further reinforce these character attributes. Conclusion: Character education should be integrated with technical expertise at the foundational level. This will enable institutions to produce competent professionals who satisfy the demands of pharmacy education and the profession.